Correction: A marine algal polyphenol, dieckol, attenuates blood glucose levels by Akt pathway in alloxan induced hyperglycemia zebrafish model. Issue 87 (5th September 2016) - Kim, Eun-A; Lee, Seung-Hong; Lee, Ji-Hyeok; Kang, Nalae; Oh, Jae-Young; Cha, Seon-Heui; Ahn, Ginnae; Ko, Seok Chun; Fernando, Shanura P.; Kim, Seo-Young; Park, Sun-Joo; Kim, Young-Tae; et al.
Abstract : Correction for 'A marine algal polyphenol, dieckol, attenuates blood glucose levels by Akt pathway in alloxan induced hyperglycemia zebrafish model' by Eun-A Kim et al., RSC Adv., 2016, 6, 78570–78575.